9-Aryl-phenalenones: Bioinspired thermally reversible photochromic compounds for photoswitching applications in the pico-to milliseconds range. (February 2021) - Bresolí-Obach, Roger; Massad, Walter A.; Abudulimu, Abasi; Lüer, Larry; Flors, Cristina; Luis, Javier G.; Rosquete, Laura I.; Grillo, Teresa A.; Anamimoghadam, Ommid; Bucher, Götz; Nonell, Santi
Abstract: Ultrafast photochromic molecules are being actively investigated to meet the demand for fast optical switching systems. Inspired on the irreversible cyclization of 9-phenylphenalenone plant metabolites to yield highly-coloured naphthoxanthenes for the purpose of defense against pathogens, aryl-substituted phenalenones have been developed that undergo a similar but reversible photochromic reaction. The lifetime of the naphthoxanthene photoisomer spans nine orders of magnitude, ranging from tens of picoseconds to tens of milliseconds depending on the electronic properties of the 9-aryl group. Graphical abstract: Image 1 Highlights: 9-Arylphenalenones are a new bioinspired family of T-type photoswitches. The photoisomer lifetime spans nine orders of magnitude from pico-to milliseconds. The photoisomer lifetime correlates with the electron density of the aryl group. 9-Pyridiniumphenalenone can be switched at 14 GHz.